A review of research status of failure modes of base-isolated structures under long-period ground motions. Issue 1 (October 2020) - Wang, Yanan; Liu, Yonghui; Peng, Bin
Abstract: As a relatively mature and effective passive damping technology, isolation technology is mostly used in engineering structures in high-intensity areas and post-earthquake reconstruction projects. In recent years, with the deepening of performance-based seismic engineering research, the study of damage failure of isolated structures under strong earthquakes has become one of the hot-spots in the field of seismic engineering research. This paper summarizes the research results of domestic and foreign scholars on the failure of the base-isolated structure under the action of long-period ground motions, and summarizes its main failure modes. Based on the main failure modes, it systematically analyzes the failure mechanism and finally points out there are still some issues to be studied.